Climate justice, speciesism, and total liberation in age of the anthropocene - Best, Steve (Frontiers in Communication, 2025)
This essay provides a critical overview of climate justice discourse, while examining a key deficit that stems from humanist/speciesist biases and a failure to incorporate nonhuman animals (hereafter “animals”) into social analyses, ethics, politics, and visions of a just transition to an ecological society. This deficit, I argue, has serious consequence for understanding the roots and driving forces of social hierarchies, mass extinction, and the climate crisis. Climate mitigation strategies, I claim, will fail without engaging animal rights and vegan perspectives. I argue that earth, animal, and human liberation movements are inseparably interlinked in a comprehensive project of “total liberation.” A guiding thread throughout is the focus on increasingly expansive concepts of rights and justice that break through the parochial boundaries of humanist views, to include “animal justice,” “multispecies justice” and “planetary justice.” These emerging moral paradigms and cognitive mappings are vital to overcome the global social and ecological crises that define the Anthropocene Epoch.